Contribution of astrocytes to hippocampal long-term potentiation through release of d-serine - Yang, Yunlei (National Academy of Sciences, 2003)
Repetitive correlated activation of pre- and postsynaptic neurons induced long-term potentiation (LTP) of synaptic transmission among hippocampal neurons grown on a layer of astrocytes (mixed cultures) but not among neurons cultured in glial conditioned medium. Supplement of d-serine, an agonist for the glycine-binding site of N-methyl-d-aspartate (NMDA) receptors, enhanced NMDA receptor activation and enabled LTP induction in glial conditioned medium cultures. The induction of LTP in both mixed cultures and hippocampal slices was suppressed by NMDA receptor antagonists, glycine-binding-site blockers of NMDA receptors, or an enzyme that degrades endogenous d-serine. By providing extracellular d-serine that facilitates activation of NMDA receptors, astrocytes thus play a key role in long-term synaptic plasticity.